The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00359-012-0775-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic patterns from fast-starts in teleost fish and their possible relevance to predator–prey interactions

Abstract: Fast-starts are distributed over a wide phylogenetic range of fish and are used for different purposes such as striking at prey or escaping from predators. Here we investigated 42 fast-starts of rainbow trouts (Oncorhynchus mykiss) elicited by a startle stimulus. We investigated the patterns of water movements left behind by the escaping fish and their possible value as a source of information to piscivorous predators that rely on hydrodynamic sensory systems. Particle image velocimetry (PIV) measurements reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These water movements provide valuable sources of information for piscivorous predators at a distance not only about the presence of a fish of suitable size but also about the species or the swimming style of the fish that have passed by at an earlier point in time (Hanke and Bleckmann, 2004). A recent study showed that the flow structures caused by the fast-starting fish consisted of multiple jets that contain directional information, which are suited to provide aquatic predators not only with information on the presence of a fish of suitable size, but also on the direction of its escape (Niesterok and Hanke, 2013). Harbor seals-piscivorous mammals-are known to use their vibrissae to haptically discriminate the water movements left behind by prey or predator, and perceive the motion path, size and shape of the object that caused the trail (Hanke, 2014).…”
Section: Information In Liquidmentioning
confidence: 99%
“…These water movements provide valuable sources of information for piscivorous predators at a distance not only about the presence of a fish of suitable size but also about the species or the swimming style of the fish that have passed by at an earlier point in time (Hanke and Bleckmann, 2004). A recent study showed that the flow structures caused by the fast-starting fish consisted of multiple jets that contain directional information, which are suited to provide aquatic predators not only with information on the presence of a fish of suitable size, but also on the direction of its escape (Niesterok and Hanke, 2013). Harbor seals-piscivorous mammals-are known to use their vibrissae to haptically discriminate the water movements left behind by prey or predator, and perceive the motion path, size and shape of the object that caused the trail (Hanke, 2014).…”
Section: Information In Liquidmentioning
confidence: 99%
“…For example, C-starts can generate strong and longlasting flow signatures (Niesterok & Hanke 2012), and swimming fish can be tracked via their wake long after they have passed. While vision, hearing, and smell are also employed, many aquatic animals possess the unique ability to detect prey or predator and even form a threedimensional map of the surroundings by sensing the velocity and pressure fields through multiple sensors distributed along their body.…”
Section: Flow Sensing In Aquatic Animals and Marine Vehiclesmentioning
confidence: 99%
“…Harbour seals can track fish-like hydrodynamic trails (Dehnhardt et al, 2001), which allows them to detect pelagic fish over extended distances. The water movements from fast-starts in fish are especially strong and remain above background noise for several minutes (Niesterok and Hanke, 2013).…”
Section: Introductionmentioning
confidence: 99%